Evaluation of tolerance to Fusarium oxysporum and Fusarium solani in Virginia-type tobacco (Nicotiana tabacum L.) varieties under controlled conditions in Northwestern Argentina - Lorena A. Berruezo (Facultad de Ciencias Agrarias. Universidad Nacional de Cuyo, 2021)
The production of tobacco (Nicotiana tabacum L.) in Argentina is centered in the northwestern region (NWA), where the incidence of root rots and stem diseases caused by Fusarium spp. has increased considerably in recent years. This study aimed to evaluate the pathogenicity levels of isolates of the F. oxysporum and F. solani complexes in different varieties of Virginia Type tobacco. The commercial varieties MB47, PVH229, NC71, K346, K326, and K394 were inoculated with six isolates of both complexes. The variables evaluated were the incidence and severity of the symptoms. The area under the disease progress curves (AUDPC) was calculated and subjected to analysis of variance (ANOVA). Also, disease epidemiological models were fitted to the experimental data. The MB47 variety was significantly less infected and the varieties K346, K326, and K394 had the highest AUDPC means, showing susceptibility to the isolates. The disease intensity curves were adequately described by the monomolecular and logistic models. The results provide, for the first time, information about the levels of tolerance to vascular wilt and root rot under controlled conditions for the main varieties of Virginia-type tobacco grown in NWA.